Eucaryotic DNA Replication Complex: Study of Structure and Function Using the Affinity Modification Technique - Khlimankov, D. Yu; Rechkunova, N. I.; Lavrik, O. I. (Biochemistry (Moscow), 2004)
Eucaryotic DNA replication complex is now one of the most intensively studied subjects of molecular biology and biochemistry. In addition to detailed studies on the structures and functions of individual DNA polymerases involved in this process, other enzymes and protein factors are also given much attention. The structures and functions of proteins in the replication complexes are studied by various approaches, including X-ray diffraction analysis. At present, this approach provides sufficient information about the structures and functions of individual biopolymers and their complexes with ligands. However, this approach is unsuitable for studies on proteins, which cannot be cloned and isolated in amounts sufficient for X-ray diffraction analysis. Moreover, this approach is inapplicable for studies on multicomponent systems, such as DNA replication and repair complexes. Furthermore, data of X-ray diffraction analysis virtually never characterize the variety of dynamic interactions in enzymatic systems. Affinity modification is an alternative and rather successful approach for studies on structure-functional organization of supramolecular structures. This approach can be used for studies on individual enzymes and their complexes with substrates and also on systems consisting of numerous interacting proteins and nucleic acids. The purpose of this review is to analyze the available data obtained by affinity modification studies on the eucaryotic replication complex.